Demokrasi Sebagai Diskursus dan Deliberasi Menurut Jűrgen Habermas - Paulus Pati Lewar; Otto Gusti Ndegong Madung (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
Abstract: This article attempts to reconstruct and analyse the Habermas’ view on democracy as discourse and deliberation. The concept of deliberative and discursive democracy is a model of criticism toward an attempt to narrow the conception about democracy simply as an institutional matter. The concept of deliberative democracy emphasizes the importance of public discursive participation of citizens by establishing critical public sphere that is the heart of democracy. Furthermore, Habermas highlights that there is no rule of law without radical democracy. Such radical democracy is expressed through the active involvement of citizens in public sphere to express ideas that have impact on political decisions and public policy. This article accentuates that the transformation of public opinion to be a political power is an ongoing process. Therefore, an authentic democracy presupposes a critical publicity and democratic political culture. Without a voluntary citizens’ initiative in this regard, a state will have no future. To support thisarguments, the writer uses literature research method by analyzing the main work of Jȕrgen Habermas on deliberative democracy namely Faktizitӓt und Geltung (Facts and Norms), as well as some secondary literatures dealing with the thoughts of Habermas on democracy.Keywords: Habermas, deliberative democracy, discourse, pluralism, state